The association between serum ferritin levels and the risk of gestational diabetes mellitus: a prospective cohort study - Shaofei Su; Shen Gao; Enjie Zhang; Jianhui Liu; Shuanghua Xie; Yue Zhang; Ruixia Liu; Wentao Yue; Chenghong Yin (BMC Pregnancy and Childbirth)
Abstract Background The relationship between serum ferritin levels and the risk of gestational diabetes mellitus (GDM) remains unclear. This study aimed to investigate the association between serum ferritin levels and the incidence of GDM. Methods We conducted a prospective cohort study involving 10,871 pregnant women from the China Birth Cohort Study. Serum ferritin levels were measured using the direct chemiluminescence method in the first and second trimesters. Baseline serum ferritin levels were categorized into five groups according to quintiles in the first trimester, and trimester-specific median values were used to divide serum ferritin levels into four subgroups. GDM was determined by a 75 g oral glucose tolerance test at 24–28 weeks of gestation. Multivariate modified Poisson regression was performed to estimate the independent relationship between serum ferritin levels and the incident GDM. Results The median serum ferritin level in the first trimester was 57.7 ng/mL, and 13.5% of participants developed GDM. After multivariate adjustment, the RRs and 95% CIs for incident GDM across baseline serum-ferritin quintiles were 1.099 (0.940–1.285), 1.228 (1.055–1.430), 1.186 (1.018–1.383) and 1.179 (1.017–1.367), respectively. Furthermore, participants with low serum ferritin levels in the first trimester that increased to high levels in the second trimester (RR = 1.376, 95% CI: 1.169–1.612) and those with consistently high serum ferritin levels in the first and second trimesters (RR = 1.351, 95% CI: 1.185–1.541) had a significantly increased risk of GDM. Conclusions Changes in serum ferritin levels are independent risk factors for GDM. These findings underscore the importance of maintaining iron metabolism at an appropriate level during early to mid-pregnancy to reduce the risk of developing GDM.